Modelling maternal obesity: unravelling prolonged and dysfunctional labour - Muir, Ronan Davidson (2017)
Maternal obesity significantly increases the risk of a prolonged and dysfunctional labour resulting in emergency caesarean delivery. As the mechanism(s) remain to be eludicated, a translatable animal model is warranted. Recently, Elmes et al (2011) illustrated the potential of the high-fat, high-cholesterol (HFHC) diet animal model to investigate maternal obesity associated uterine dystocia, but it remains to be fully evaluated. The aim of this thesis was to evaluate this animal model by assessing the effect of a HFHC diet upon uterine contractility, and to highlight the potential mechanism(s) responsible. All female Wistar rats were sustained on a control (CON) or HFHC diet prior to and during pregnancy and labour, with tissue collected from these animals upon term delivery of the 1st pup. Uterine contractility was assessed through ex vivo contractility studies and in vivo intra-uterine telemetry surgery. Chronic exposure to a HFHC diet resulted in an aberrant asynchronous multiphasic spike bundle contraction phenotype ex vivo, with HFHC animals displaying a prolonged duration of labour up to 12 hours longer than CON animal’s in vivo. These results are reflective of human clinical studies, highlighting the efficacy and translatability of this animal model, but the mechanism(s) remain to be identified. Enzyme-linked immuno-sorbent assay and western blotting revealed that HFHC animals displayed significantly increased circulating progesterone at term, coupled with a decrease in uterine contractile-associated protein (CAP) expression including connexin-43 and caveolin-1 at the onset of term-labour (TL). Further to this, chronic exposure to a HFHC diet significantly increased circulating cholesterol, which could alter uterine myocyte membrane fluidity and compromise the expression and function of their integral CAP’s including the oxytocin receptor (OXTR); OXTR expression was increased at TL but HFHC animals displayed a protract response to this uterotonin ex vivo. Feeding of a HFHC diet significantly increased circulating oleic acid and decreased arachidonic acid, which could explain lower plasma concentrations of the utertonin prostaglandin F2α identified during a previous pilot study, and offer another potential mechanism by which maternal obesity could compromising the outcomes of labour. This thesis has highlighted the efficacy and translatability of this animal model in the study of maternal obesity associated uterine dystocia, and offered insights into the mechanism(s) responsible.